PENGARUH PEMASANGAN GIPSUM PADA KNALPOT DAN PUTARAN MESIN TERHADAP KADAR EMISI GAS BUANG CO PADA MOTOR YAMAHA MIO AT TAHUN 2010 - Haryanto, Dwi (Jurnal Nosel, 2013)
The purposes of the research were : (1) to do research effect of gypsum on CO exhaust gas emission level of Yamaha MIO AT motorcycle 2010. (2) To do research effect of rotation engine on CO exhaust gas emission level of Yamaha MIO AT motorcycle 2010. (3) To do research interactive effect installation gypsum and rotation engine on CO exhaust gas emission level of Yamaha MIO AT motorcycle 2010. Based on the data analysis, it can be concluded that: (1) There were effect installation gypsum on muffler on CO exhaust gas emission level of Yamaha MIO AT motorcycle 2010 and from the data presented indicate that the level emission of CO were lower than before using gypsum. (2) There were effect rotation engine on CO exhaust gas emission level of Yamaha MIO AT motorcycle 2010 and from the data presented indicate that the level emission of CO were lower when rotation engine 2500 rpm than rotation engine 1500 rpm and 3500 rpm. (3) There were interactive effect insatallation gypsum and rotation engine on CO and exhaust gas emission level of Yamaha MIO AT motorcycle 2010 and shows the level emission of CO more lower. (4) The lowest CO exhaust gas emission level of 5.57% volume was found by the use of gypsum II (thickly 10 mm) and with rotation engine 2500 rpm.Keywords : Gypsum, Rotation Engine, CO Exhaust Gas Emission